Chinese Families’ Pursuit of Confucian Learning Beliefs through Overseas Education: Rethinking Learning Cultures in Cross-Cultural Research - Chen, Juan (Journal of Education Culture and Society, 2023)
Aim. The aim of the article is to understand how Chinese parents draw on their learning beliefs and experiences within the Chinese educational context to make decisions about their children’s overseas education, as well as analysing how their learning beliefs are similar or different from East Asian or Western learning beliefs.Methods. The study is based on more than 100 in-depth separate interviews with 22 Chinese families conducted over serval years between 2016 and 2019. Based on interpretative phenomenological analysis and discourse analysis, the results are coded according to the theory of values proposed by Clyde Kluckhohn (1951). These learning values are further coded according to whether they are reflective of the American learning model (EALM), Confucian learning model (CLM), and Confucian learning philosophies.Results. The analysis shows that Chinese parents have displayed similar learning beliefs in socialising their children in the family domain, in their disapproval of the Chinese education system, and in their pursuit of a Western overseas education. The Chinese families’ pursuit of a Western education for their children are driven by their cultural leaning beliefs, which are rooted in Confucian heritage culture, and which also echo European American heritage cultures.Conclusion. Many researchers tend to emphasise cultural differences in learning, particularly between Confucian heritage and European American heritage cultures. This paper shows the possibilities of cultural learning values shaping educational choices, expands upon the understanding of Confucian heritage culture, and suggests the similarities between the learning cultures of East Asia and the West.